(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to improve student learning outcomes through the application of the two-stay two-stray learning model in Mathematics learning. This research was conducted at SD Negeri 004 Rambah Samo with the research subject of grade IV students totaling 20 students. Each cycle is carried out 2 meetings, where at the end of each learning test is carried out to find out the learning results obtained by students. Data collection techniques are carried out in the form of student activity observation sheets, teacher activity observation sheets and question tests. The learning outcomes of students before conducting research on mathematics learning were obtained by students who completed 50% and those who did not complete 50%. After learning mathematics using the two-stay two-stray learning model, the results obtained in cycles I and II increased in students’ average scores and learning activities. Based on the results of the research that has been carried out, it can be concluded that the application of the learning strategy of the two stay two stray learning model can improve the mathematics learning outcomes of grade IV students of SD Negeri 004 Rambah Samo